A brief and visual history of antisemitism - Bitton, Israel B. 1984- (Gefen Publishing House, 2022)
"The world is in crisis: antisemitism, the “longest hatred,” is rearing its ugliest heads, again. Although much has been written about the subject, very little has been done to educate the public specifically about antisemitism—existing curricula are either outdated or not comprehensive, and none are designed to be engaging, especially to the younger audiences that need to learn this subject most. A Brief and Visual History of Antisemitism aims to fill that glaring gap, not merely as a history textbook but as an epidemiological study that analyzes the pathology of the antisemitism virus from ancient to modern times: when, where, and how did antisemitism first emerge? How did the disease of Jew-hatred spread so far and wide? Why has the hateful virus proven so resilient over time? The goal of this highly visual book is thus not merely to inform of what has already transpired, but to empower individuals to make sense of the avalanche of anti-Jewish invective in real-time. As an added feature, Augmented Reality technology allows readers to use their phones (and a free app) to scan highlighted areas and reveal a trove of bonus contents such as archival footage, animations, official documents, and 3D objects that offer immersive perspectives on historical landmarks."